Enkele opmerkings oor die godsdienstig- teologiese insigte wat na vore kom in die Gelofte van 1838 en daarna by die onderhouding daarvan - A. D. Pont (HTS Teologiese Studies/Theological Studies, 2000)
Some remarks on the theological insights on the Voortrekker Vow of (16 December) 1838 which contributed to the continued honouring of the Vow. In this study it is noted that after the Batle of Colenso on 15 December 1899 and the Batle of Nooitgedacht on 13 December 1900, the Boer commandos held special meetings to commemorate the Voortrekker Vow of 1838 and the victory at Blood River. The question is asked what the theological background can be. When the Voortrekker Vow of 1838 is studied it becomes clear that the taking of the Vow was possible in the context of the Calvinist orthodoxy, influenced by the Nadere Reformatie of the 17'h Century. This was more or less the accepted theology of the Voortrekkers sustained by the Statenbijbel and the books of the Nadere Reformatie theologians.